The wage curve reloaded - David G. Blanchflower; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2005)
This paper provides evidence for the existence of a wage curve - a micro-econometric association between the level of pay and the local unemployment rate - in modern U.S. data. Consistent with recent evidence from more than 40 other countries, the wage curve in the United States has a long-run elasticity of approximately -0.1. In line with the paper's theoretical framework: (i) wages are higher in states with more generous unemployment benefits, (ii) the perceived probability of job-finding is lower in states with higher unemployment, and (iii) employees are less happy in states that have higher unemployment. We conclude that it is reasonable to view the wage curve as an empirical law of economics.
Keywords: J3; E2; 330; wages; unemployment; wage curves; Lohn; Arbeitslosigkeit; Theorie; Welt